Market Segmentation, Information Asymmetry and Investor Responses in the Chinese A- and B-Markets - Juan Yao (Australasian Accounting, Business and Finance Journal, 2014)
This paper examines changes in returns and trading volumes around earnings announcements for firms which have both A-shares (traditionally for local investors only) and B-shares (traditionally for foreign investors only) in China. It considers the impact of regulatory changes which reduced the segmentation of local and foreign investors across the two classes of shares. We find that both the A- and B-markets experience significant price changes around earning announcements. When the two markets are fully segmented, the magnitude of price changes in the A-share market are significantly smaller than the B-market which lends empirical support to the previous claim that the B-market is less informed. The changes in trading volume indicate that the B-market investors have less divergent expectations and interpretations of the pre-disclosure information compared to the A-market investors.However, when regulatory changes reduced the level of segmentation, the price and volume reactions in the two markets became more consistent. The results suggest that the A- and Bmarkets are more integrated as a result of the regulatory changes.
Keywords: Earnings announcements; Chinese Stock Markets